Assessment of Knowledge, Attitude, and Practice toward Antibiotic Use among Harar City and Its Surrounding Community, Eastern Ethiopia - Jifar, ALemnesh; Ayele, Yohanes (Interdisciplinary Perspectives on Infectious Diseases, 2018)
Purpose. Community plays significant role in the process of emergence and spread of antibiotic resistance. The aim of this study is to assess knowledge, attitude, and practice toward antibiotic use among Harar city and its surrounding community, Eastern Ethiopia. Patient and Methods. A cross-sectional study was conducted among 384 subjects from February 1 to May 1, 2017, through interview using pretested structured questionnaires. The data was entered into EpiData 3.1 and analyzed using Statistical Package for Social Science for windows version 20. Results. A large number of the respondents (83%) replied that antibiotics speed up the recovery from coughs and colds. The majority of participants (78.4%) agreed that the unnecessarily use of antibiotics can increase the resistance of bacteria. Many respondents agreed on the importance of taking full dose (92.1%) and not to keep antibiotics for future use in their home (87.2%). They (90%) also had belief that antibiotics should not be shared from family or friends without a physician consultation and significant participants (73.1%) emphasized on the need for prescription to collect antibiotics from pharmacy. Around 79% of the subjects reported the use of antibiotic 1 year prior to study period at least once. During this period many subjects (65.3%) self-prescribed antibiotics without consulting physicians. Conclusion. In the present study, widespread use of antibiotics was reported, most of this antibiotics being accessed without prescription. Respondent exhibited poor knowledge and attitude toward antibiotics use. There were also malpractices such as failing to take full dose. Therefore, educational interventions on antibiotics use and its association with drug resistance are needed to promote judicious use of antibiotic. Introducing and enforcing antibiotics regulations should be also considered to reduce antibiotics self-prescription.